Architecting for Digital Inclusion: Building and Training for Accessible Web Systems at Scale - Murali Ajit Varma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Digital inclusion has emerged as a critical architectural consideration in modern web development, fundamentally reshaping how organizations approach system design and implementation. This article presents a comprehensive framework for building accessible web systems at scale, exploring the integration of accessibility throughout the technical stack. It examines component-level architecture patterns, performance optimization strategies, and DevOps practices that enable truly inclusive digital experiences. Through analysis of real-world implementations and industry case studies, this study demonstrates how systematic approaches to accessibility can be effectively scaled across large organizations while maintaining performance and developer efficiency. It also indicates that early integration of accessibility considerations into architectural decisions leads to more sustainable and inclusive systems, reducing technical debt and improving user experiences across diverse populations. Drawing from established research and industry practices, this article contributes to the growing knowledge on scalable accessibility implementation, offering practical insights for technical leaders and development teams building enterprise-scale accessible web systems.
Keywords: Digital Accessibility Architecture; Web Systems Engineering; Inclusive Design Patterns; DevOps Accessibility Integration; Performance Optimization; Enterprise-scale accessibility; Accessibility Framework; Component-Level Architecture